For this case we have the following system of equations:
![x-3y = -13\\5x + 7y = 34](https://img.qammunity.org/2020/formulas/mathematics/college/zfh6g275i94vl2hs38dadpc7qtvwhza8ox.png)
From the first equation we clear "x":
![x = -13 + 3y](https://img.qammunity.org/2020/formulas/mathematics/college/1kqo6n1a2zklz0kisl08lt3bzmofmuw45o.png)
We substitute in the second equation:
![5 (-13 + 3y) + 7y = 34](https://img.qammunity.org/2020/formulas/mathematics/college/k41cctqfd8g3o9lop2uwd0wta4wta3sjhr.png)
We apply distributive property:
![-65 + 15y + 7y = 34](https://img.qammunity.org/2020/formulas/mathematics/college/qv7ukriwkmtka5y8ezsk0e7018mokqwok6.png)
We add similar terms:
![-65 + 22y = 34](https://img.qammunity.org/2020/formulas/mathematics/college/pjvqrrt7nhy255wz88mcm7hvwgjh40yjwc.png)
We add 65 to both sides:
![22y = 34 + 65\\22y = 99](https://img.qammunity.org/2020/formulas/mathematics/college/13cpfuwl678q634gpoa3sm5m0ibeonatfm.png)
We divide between 22 on both sides:
![y = \frac {99} {22}\\y = \frac {9} {2}](https://img.qammunity.org/2020/formulas/mathematics/college/wpfgg9yu5dcujs4k02zzj7u8mdqg2tibfl.png)
We look for the value of the variable "x":
![x = -13 + 3 \frac {9} {2}\\x = -13 + \frac {27} {2}\\x = \frac {-26 + 27} {2}\\x = \frac {1} {2}](https://img.qammunity.org/2020/formulas/mathematics/college/ltchzxltv7cuh9y91cipwg11e9zbn6a9ff.png)
Thus, the solution of the system is:
![(x, y): (\frac {1} {2}, \frac {9} {2})](https://img.qammunity.org/2020/formulas/mathematics/college/r3dvddd9uhjy9ojzimircj0mlic9afap2g.png)
ANswer:
![(x, y): (\frac {1} {2}, \frac {9} {2})](https://img.qammunity.org/2020/formulas/mathematics/college/r3dvddd9uhjy9ojzimircj0mlic9afap2g.png)